SPEED REGULATION OF INDUCTION MOTOR WITH PWM INVERTER (ETIMA, 2021)
AbstractThis paper presents the speed regulation of a 2.2 kW asynchronous squirrel-cage motor, a product of companyRade Koncar, with the aid of a voltage inverter controlled by the pulse-width modulation principle. The simulationcircuit is developed in software Powersim. The exact motor data are input in the simulation model and theoperation of the motor is simulated for various operating frequencies of the inverter. As an output, the transientcharacteristics of speed, current, and torque are obtained at various operating speeds i.e. below and above therated speed of the motor. The effect of the field weakening is observed at higher operating speeds. Obtained resultsof speed, torque, and currents are compared with the motor data obtained from the analytical model of the motorand data of the manufacturers of variable speed drives, for operating regimes different than the rated. Thesimulation can serve as an example that proves the theoretical principles of pulse-wide modulation where thedesired motor speed is easily obtained with the variation of frequency of modulating signal of the inverter.KeywordsAsynchronous squirrel cage motor, PWM inverter, field –weakening, transient characteristics